Sonochemically synthesized cobalt oxide nanoparticles as an additive for natural polymer iodide electrolyte based dye-sensitized solar cells - Goh, Z. L. (Elsevier, 2022)
Hydroxypropyl cellulose (HPC)-based gel polymer electrolytes with different alkali metal iodide salts (potassium iodide, KI; sodium iodide, NaI; and lithium iodide, LiI) were investigated. Electrochemical impedance spectroscopy (EIS) was used to examine the electrochemical properties of the electrolytes. The electrolyte containing KI salt (KI sample) has the highest ionic conductivity. The trend of conductivity of the samples developed as follows, KI > NaI > LiI. A hybrid gel polymer electrolyte (HGPE) was developed to further enhance the property by incorporating sonochemically synthesized cobalt oxide (Co3O4) nanoparticles into the KI sample. The nanoparticles were studied by field emission scanning electron microscopy (FESEM), high-resolution transmission electron microscopy (HRTEM), energy-dispersive X-ray spectroscopy (EDX), X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS). HGPEs containing various amounts of synthesized Co3O4 nanoparticles were examined with EIS, XRD, and Linear Sweep Voltammetry (LSV). The introduction of Co3O4 nanoparticles has improved the ionic conductivity, reduced activation energy and degree of crystallinity of the HGPEs. Dye sensitized solar cells (DSSCs) assembled with the developed HGPEs have shown an improvement in short-circuit current density and efficiency. HGPE containing 7 wt% of Co3O4 nanoparticles achieved the best ionic conductivity and photovoltaic performance of DSSC of 8.02 mS cm(-1) and 5.8%, respectively.